Trends of young players towards playing positions in football in Khartoum State - Ahmed Mahmoud Awad, Yes; Ibrahim Al-Tayeb, Hajj (sports creativity, 2025)
This study aimed to identify the preferences of young footballers towards different positions in Khartoum State. The researcher used a descriptive methodology, and the sample consisted of 418 randomly selected young footballers. A questionnaire was used as the data collection tool. The most important findings were: the study revealed that the majority of young players preferred the midfield position, followed by the defense, then the attack, and finally the goalkeeper position. The most important recommendations include: encouraging young players to pursue the less popular positions, particularly attack and goalkeeper; and emphasizing the crucial role of training centers and coaches in developing and nurturing talent, as well as providing training programs to guide young players towards their preferred positions.